2002
DOI: 10.1046/j.1359-4117.2002.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate decreases VEGF production in head and neck and breast carcinoma cells by inhibiting EGFR‐related pathways of signal transduction

Abstract: In a recent study on head and neck squamous cell carcinoma (HNSCC) cells we found that epigallocatechin-3-gallate (EGCG), a major biologically active component of green tea, inhibited activation of the epidermal growth factor receptor (EGFR) and related signaling pathways. Since activation of EGFR signaling pathways is associated with angiogenesis, we examined the effects of EGCG on vascular endothelial growth factor (VEGF) production by YCU-H891 HNSCC and MDA-MB-231 breast carcinoma cell lines, because we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
155
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(168 citation statements)
references
References 18 publications
9
155
0
4
Order By: Relevance
“…GTE treatment was well tolerated, although higher doses increased insomnia and nervousness (albeit without grade 4 toxicities). This study also provided some very important biomarker data, including data on VEGF that are consistent with previously reported effects of GTE (18,31). Baseline stromal VEGF levels correlated with clinical (P = 0.04) but not histologic response.…”
supporting
confidence: 69%
“…GTE treatment was well tolerated, although higher doses increased insomnia and nervousness (albeit without grade 4 toxicities). This study also provided some very important biomarker data, including data on VEGF that are consistent with previously reported effects of GTE (18,31). Baseline stromal VEGF levels correlated with clinical (P = 0.04) but not histologic response.…”
supporting
confidence: 69%
“…Flavonoids, of which soy-based isoflavones are the most intensely studied, lower endogenous hormone levels in pre- (Dai et al, 2002;Ren et al, 2003) and post-menopausal women (Murkies et al, 1995), and inhibit transcriptional factors involved in cancer metastasis (Valachovicova et al, 2004;Slivova et al, 2005), including vascular endothelial growth factor, which is strongly associated with tumour angiogenesis (Masuda et al, 2002). These findings provide support for a biologically plausible association between dietary intake of flavonoids, particularly isoflavones, on breast cancer risk and prognosis.…”
supporting
confidence: 54%
“…22,23 EGCG has also been shown to inhibit endothelial cell proliferation, VEGF receptor binding, VEGFR-2 phosphorylation, VEGFR-2 expression and matrix metalloproteinase activity in endothelial cells, all processes integral to angiogenesis. [23][24][25][26][27][28][29] In a respiratory epithelial cell line, Chen et al 30 reported that EGCG can inhibit IjB kinase (IKK) activation and IL-8 gene expression. However, most of these reports on EGCG have been achieved using very high and physiologically unrealistic doses of the catechin.…”
mentioning
confidence: 99%